Calculation and study of the failure of the connecting-rod small end based on thermoelastic plasticity. (September 2017) - Chen, Guohua; Liao, Ridong; Jiang, Xue
In this study, the mechanisms that cause bush loosening and rotation failure were studied on the connecting-rod small end of a high-power-density engine. Using the thermoelastic plasticity model and the thermomechanical coupling method, the stress field and the assembly contact force of the connecting-rod small end were predicted by considering four different loading conditions: first, the initial loading condition; second, the thermal loading condition; third, the mechanical loading condition; fourth, the unloading condition. This process showed the effects of the initial interference fit, the operating temperature and the wall thickness of the bush on the assembly contact force. It was found that, first, a large interference leads to a small assembly contact force after unloading, second, a higher operating temperature significantly reduces the assembly contact force and, third, the wall thickness of the bush has little influence on the assembly contact force. In conclusion, a high operating temperature is the main cause of bush loosening and rotation. This conclusion was validated by the experimental results. On the basis of this study, it is suggested that the operating temperature is limited in order to maintain the reliability of the connecting-rod small end.